Report on the differences in the law of England and Ireland as regards the protection of women - Brooke, William G. (Statistical and Social Inquiry Society of Ireland, 1873)
In the execution of the task you have entrusted to me?namely, to report on the difference in the Law of England and Ireland, as regards the Protection of Women?I shall endeavour to confine my remarks within the strict limits of the subject. It will not, therefore, lie within my province to enter upon any general examination of the laws relating to the position of women, nor to dwell upon any subjects, however interesting or prominent they may be, as to which the law in both countries presents no variety of feature.
Read before the Society, 21 January 1873
Keywords: Protection of women in Irish law; Illegitimate children; Women's rights; Education of women; 314.15